Solar Geoengineering Modeling and Applications for Mitigating Global Warming: Assessing Key Parameters and the Urban Heat Island Influence - Feinberg, Alec (Frontiers in Climate, 2022)
In this paper, solar geoengineering modeling is presented with a goal to simplify reverse forcing assessments and the capability to apply it to a wide variety of applications. Results find improvements on sun-shade space mirror and desert surface treatment estimates, stratosphere sun-dimming methods, and the Urban Heat Islands (UHIs) influence. A heat amplification parameter is added to the model allowing it to be applied to UHI estimates. UHI amplification effects are due to the large solar area of buildings, reduction of wind cooling, solar canyons, and so forth. The UHI reverse forcing requirements are assessed with amplification estimates of 3.1 and 5.2, yielding 7.6% to 12.7% of gross global warming could be due to the urbanization effect, respectively. The gross warming 7.6% estimate, accurately compares to the author's prior study, and the 12.7% represents very recent results by other authors from new measurement methods. Key issues are pointed out that without including a heat amplification estimate and other modeling parameters, the UHI intensity, that likely dominates the urbanization warming effect could be severely underestimated, yielding urbanization estimates possibly as low as 2.4%. It is important to identify possible reasons where underestimates may occur from a modeling perspective to help understand controversies that may be occurring. The new model helps to clarify such parameters, allows for a significant reduction in complexity and calibration, and is shown to be helpful for numerous solar geoengineering applications including the serious need to reduce the UHI effect worldwide. Solar geoengineering solutions will require a lot of creativity, in addition to modeling, suggestions are provided for drought relief ideas and Paris Accord goals required for any successful urban solar geoengineering coordinated effort.